Pengaruh Model Inquiry terhadap Kemampuan Memahami Teks Deskripsi pada Siswa SMP - Maulida Sari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
The learning model is one of the important aspects of teaching. The learning model can be determined and chosen by the teacher correctly so that it is appropriate and able to teach students. The purpose of this study was to explain the effect of the inquiry learning method on the learning abilities of class VII students in the material description text. The research sample was 34 students of class VII SMP Negeri 3 Langsa City. The research method used is quasi-experimental. Research data were collected through test techniques. The research design used was a pretest-posttest control group design. Based on the application of the method, it was found that the use of the Inquiry Learning method could improve student learning outcomes. This is evidenced by the results of the t-test with the value of Sig. (2-tailed) of 0.000 < (0.05). Inquiry learning classes have increased by 26%. Judging from the percentage, the inquiry class is better at improving the learning outcomes of class VII students of SMPN 3 Langsa City, especially in the description text material.